Fare-Free Transit Evaluation Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Recognizing the strong recent interest throughout the United States to consider and implement fare-free transit, decision-making tools are needed to help public transit practitioners evaluate fare-free transit.The TRB Transit Cooperative Research Program's TCRP Research Report 237: Fare-Free Transit Evaluation Framework presents a framework that can be used by public transit practitioners to evaluate the potential benefits, costs, and trade-offs of implementing fare-free transit.Supplemental to the report is an Infographic.
Keywords: Transportation and Infrastructure

Measurement and Analysis of Public Opinion: An Analytic Framework - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Intelligence analysts conduct these analyses every day, using decades of propriety tradecraft techniques and an arsenal of clandestine information gathering sources, but the resources available are not unlimited. Open source public opinion tools can provide timely and relatively inexpensive methods of understanding fast-moving conditions, acting as a force multiplier to help policymakers have a truly all-source understanding of complex events. By providing analysts with the best practices in survey methodology and nonsurvey methods for gathering data on public opinion, they will be armed with a clearer sense of important shifts in attitudes, elections, and unrest. In order to provide guidance to analysts on strategies for assessing public opinion, representatives from the intelligence community approached the National Academies of Sciences, Engineering, and Medicine to request preparation of a framework on Measuring and Analyzing Public Opinion. This analytic framework includes three layers of information. Layer 1 comprises four authored papers that review literature from various disciplines containing overview information as well as how the topic/situation of interest can enable better analysis across different situational constraints. Layer 2 is a distilled layer of information in the form of an authored summary of the four Layer 1 papers, both summarizing and describing key points. Finally, Layer 3 provides an even further distillation of the key concepts, in a one-page visual graphic, that displays key drivers from the work in Layers 1 and 2 to help the intended audience apply knowledge to the situation of interest.
Keywords: Behavioral and Social Sciences

Implementation of Life-Cycle Planning Analysis in a Transportation Asset Management Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Highway infrastructure assets are designed and built to serve long, useful lives. These assets undergo structural aging and degradation driven by traffic and environmental factors, natural and human hazards, and changes in demand and functional use. NCHRP Web-Only Document 365: Implementation of Life-Cycle Planning Analysis in a Transportation AssetManagement Framework, from TRB's National Cooperative Highway Research Program, develops a framework to perform life-cycle planning and is supplemental to NCHRP Research Report 1065: Life-Cycle Planning Analysis in a Transportation Asset Management Framework.
Keywords: Transportation and Infrastructure

Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design (The National Academies Press, 2023)
Since the inception of using sets of plans for construction purposes, a persistent challenge has been the miscommunication between designers and constructors, even when they were part of the same organization. NCHRP Web-Only Document 388: Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design, from TRB's National Cooperative Highway Research Program, develops a decision-making framework that is scalable to all contract delivery methods and that complies with all environmental statutory requirements. Supplemental to the report are a technical memorandum, an adaptation guide for the framework toolkit, a full presentation, and an abridged presentation.
Keywords: Transportation and Infrastructure

Life-Cycle Planning Analysis in a Transportation Asset Management Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Life-cycle planning (LCP) is an integral part of the transportation asset management (TAM) framework. LCP is a process that estimates the full cost of managing an asset over its anticipated useful life. It is a practice based on economic and engineering principles to facilitate the development of a life-cycle activity plan for a given asset that balances costs, risks, and expected performance. NCHRP Research Report 1065: Life-Cycle Planning Analysis in a Transportation Asset Management Framework, from TRB's National Cooperative Highway Research Program, provides transportation planning and engineering professionals with a guide to the implementation of LCP analysis to support TAM. Supplemental to the report are NCHRP Web-Only Document 365: Implementation of Life-Cycle Planning Analysis in a Transportation Asset Management Framework, a summary of findings, an implementation plan, and a webinar presentation.
Keywords: Transportation and Infrastructure

Primer and Framework for Considering an Airport Noise and Operations Monitoring System - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Airports use Noise and Operations Monitoring Systems (NOMSs) to collect, manage, analyze, and communicate data such as flight tracks and procedures, aircraft identification, noise measurements, noise abatement program performance, and weather. NOMSs are also used to respond to community noise complaints and provide stakeholders with information about aircraft activity and noise, thus fostering trust and transparency.The TRB Airport Cooperative Research Program's ACRP Research Report 237: Primer and Framework for Considering an Airport Noise and Operations Monitoring System is a comprehensive resource to help airport industry practitioners assess the potential benefits and costs of acquiring, maintaining, and updating a NOMS or flight tracking tools without permanent noise monitors.Supplemental to the report are Appendices A though K.
Keywords: Transportation and Infrastructure

Developing a Highway Framework to Conduct an All-Hazards Risk and Resilience Analysis - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Transportation agencies currently have to meet federal regulations that require the incorporation of risk and resilience into their activities, including MAP-21, FHWA 5520, and the Infrastructure Investment and Jobs Act. However, guidelines for analytical risk assessment methods to support risk-based processes is lagging. The TRB National Cooperative Highway Research Program's NCHRP Research Report 1014: Developing a Highway Framework to Conduct an All-Hazards Risk and Resilience Analysis presents a research roadmap to develop a comprehensive manual, tools, training, and implementation guidelines for quantitative risk and resilience assessment that satisfies new federal requirements. Supplemental to the report are an implementation and communications plan, a flyer summarizing the project, and a PowerPoint presentation.
Keywords: Transportation and Infrastructure

Discussion Draft of the Preliminary Framework for Equitable Allocation of COVID-19 Vaccine - National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On September 1, 2020, the National Academies of Sciences, Engineering, and Medicine invited public comment on the Discussion Draft of the Preliminary Framework for Equitable Allocation of COVID-19 Vaccine, commissioned by the Centers for Disease Control and the National Institutes of Health. Input from the public, especially communities disproportionately affected by the COVID-19 pandemic, is essential to produce a final report that is objective, balanced, and inclusive. The public comment period was open for 4 days, from 12:00 p.m. ET on Tuesday, September 1, until 11:59 p.m. ET on Friday, September 4. In addition, the study committee hosted a listening session on Wednesday, September 2, from 12:00 to 5:00 p.m. ET to hear comments from the public. For more information, please visit the study webpage. If you have any questions, please email COVIDVaccineFramework@nas.edu.
Keywords: Health and Medicine

Framework for Assessing Potential Safety Impacts of Automated Driving Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Quickly advancing automated driving system (ADS) technologies are expected to positively affect transportation safety. ADS includes a plethora of applications that affect safety, mobility, human factors, and environmental aspects of driving. TRB's joint publication of the National Cooperative Highway Research Program and the Behavioral Transportation Safety Cooperative Research Program is titled NCHRP Research Report 1001/BTSCRP Research Report 2: Framework for Assessing Potential Safety Impacts of Automated Driving Systems. The report describes a framework to help state and local agencies assess the safety impact of ADS and is designed to guide them on how to adapt the framework for a variety of scenarios. Supplemental to the report are a Video describing the project’s assessment framework, a Proof of Concept Results Document, an Implementation Plan, and a Future Research Needs Document.
Keywords: Transportation and Infrastructure

Mobility on Demand and Automated Driving Systems: A Framework for Public-Sector Assessment - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Innovative and emerging mobility services offer travelers more options to increase mobility and access goods and services. In addition, various technological developments have the potential to alter the automotive industry and traveler experience, as well as mobility and goods access. The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 331: Mobility on Demand and Automated Driving Systems: A Framework for Public-Sector Assessment provides resources that identify key stakeholders and partnerships, offers emerging lessons learned, and provides sample regulations that can be used to help plan for and integrate emerging modes. The document is supplemental to NCHRP Research Report 1009: Shared Automated Vehicle Toolkit: Policies and Planning Considerations for Implementation.

Investing in Transportation Resilience: A Framework for Informed Choices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Significant progress has been made over the last decade in integrating resilience criteria into transportation decision-making. A compelling case remains for investing in making transportation projects more resilient in the face of increasing and intensifying storms, floods, droughts, and other natural hazards that are combining with sea-level rise, new temperature and precipitation norms, and other effects from climate change.TRB’s Special Report 340: Investing in Transportation Resilience: A Framework for Informed Choices reviews current practices by transportation agencies for evaluating resilience and conducting investment analysis for the purpose of restoring and adding resilience. These practices require methods for measuring the resilience of the existing transportation system and for evaluating and prioritizing options to improve resilience by strengthening, adding redundancy to, and relocating vulnerable assets.Supplemental to the report is a Report Highlights three-pager.
Keywords: Transportation and Infrastructure

Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 8-9, 2022, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop, Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks. The workshop examined the collection, interpretation, and use of location data by government, academia, and industry. This publication summarizes the presentations and discussion of the workshop.
Keywords: Computers and Information Technology

Identification of Factors Contributing to the Decline of Traffic Fatalities in the United States from 2008 to 2012 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Between 2005 and 2011, the number of traffic fatalities in the U.S. declined by 11,031, from 43,510 in 2005 to 32,479 in 2011. This decline amounted to a reduction in traffic-related deaths of 25.4 percent, by far the greatest decline over a comparable period in the last 30 years.Historically, significant drops in traffic fatalities over a short period of time have coincided with economic recessions. Longer recessions have coincided with deeper declines in the number of traffic fatalities. This TRB National Cooperative Highway Research Program's NCHRP Research Report 928: Identification of Factors Contributing to the Decline of Traffic Fatalities in the United States from 2008 to 2012 provides an analysis that identifies the specific factors in the economic decline that affected fatal crash risk, while taking into account the long-term factors that determine the level of traffic safety.A key insight into the analysis of the factors that produced the sharp drop in traffic fatalities was that the young contributed disproportionately to the drop-off in traffic fatalities. Of the reduction in traffic fatalities from 2007 to 2011, people 25-years-old and younger accounted for nearly 48 percent of the drop, though they were only about 28 percent of total traffic fatalities prior to the decline. Traffic deaths among people 25-years-old and younger dropped substantially more than other groups. Young drivers are known to be a high-risk group and can be readily identified in the crash data. Other high-risk groups also likely contributed to the decline but they cannot be identified as well as age can.
Keywords: Transportation and Infrastructure

Practitioner’s Guide to the Integrated Ecological Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-C06-RW-3: Practitioner’s Guide to the Integrated Ecological Framework explores ways to apply ecological principles early in the planning and programming process of highway capacity improvements to inform environmental reviews and permitting. The guide is part three of a four-volume set. Other volumes in the set include:An Ecological Approach to Integrating Conservation and Highway Planning, Volume 1 summarizes the research approach and major findings of a project designed to help transportation and environmental professionals apply ecological principles early in the planning and programming process of highway capacity improvements to inform later environmental reviews and permitting.An Ecological Approach to Integrating Conservation and Highway Planning, Volume 2 is a summary of the approach and outcomes of a partner project, Integration of Conservation, Highway Planning, and Environmental Permitting through Development of an Outcome-Based Ecosystem-Scale Approach and Corresponding Credit System.The fourth volume, Manager’s Guide to the Integrated Ecological Framework provides a basic understanding of the Integrated Ecological Framework (IEF), a nine-step process for integrating ecological and transportation planning.A supplemental report, Integrated Ecological Framework Outreach Project, documents the techniques used to disseminate the project's results into practitioner communities and provides technical assistance and guidance to those agencies piloting the products.The primary product of these complementary efforts is the Integrated Ecological Framework (IEF). The IEF is a step-by-step process guiding the integration of transportation and ecological planning. Each step of the IEF is supported by a database of case studies, data, methods, and tools. The IEF is available through the Transportation for Communities – Advancing Projects through Partnerships (TCAPP) website.
Keywords: Transportation and Infrastructure

Manager’s Guide to the Integrated Ecological Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) S2-C06-RW-4: Manager’s Guide to the Integrated Ecological Framework is designed to provide a basic understanding of the Integrated Ecological Framework (IEF), a nine-step process for integrating ecological and transportation planning. It presents information about the relevant stakeholders and types of expertise needed to help ensure positive transportation infrastructure and conservation outcomes. The guide also includes updates to earlier documents developed for the C06 project. The guide is available in electronic format only.The guide is part four of a four-volume set. Other volumes in the set include:An Ecological Approach to Integrating Conservation and Highway Planning, Volume 1 summarizes the research approach and major findings of a project designed to help transportation and environmental professionals apply ecological principles early in the planning and programming process of highway capacity improvements to inform later environmental reviews and permitting.An Ecological Approach to Integrating Conservation and Highway Planning, Volume 2 is a summary of the approach and outcomes of a partner project, Integration of Conservation, Highway Planning, and Environmental Permitting through Development of an Outcome-Based Ecosystem-Scale Approach and Corresponding Credit System.The third volume, Practitioner’s Guide to the Integrated Ecological Framework, describes the IEF and outlines a way to integrate the conservation and restoration needs and objectives of multiple entities.A supplemental report, Integrated Ecological Framework Outreach Project, documents the techniques used to disseminate the project's results into practitioner communities and provides technical assistance and guidance to those agencies piloting the products.Each step of the IEF is supported by a database of case studies, data, methods, and tools. The IEF is available through the Transportation for Communities – Advancing Projects through Partnerships (TCAPP) website. TCAPP will be re-launched at a future date as “PlanWorks” by the Federal Highway Administration.
Keywords: Transportation and Infrastructure

Framework for a Pavement-Maintenance Database System - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Report 820: Framework for a Pavement-Maintenance Database System provides a uniform format for collecting, reporting, and storing information on pavement-maintenance actions. The framework may facilitate usage of the data in cost-benefit analyses, evaluation of the effects of maintenance on pavement performance, selection of maintenance actions, and other related decisions.Accompanying the report, are a DVD and a CD that can be downloaded as ISO images. Volume 1: Framework is a DVD that contains the the Pavement-Maintenance Database (PMDb). VMware Player can be downloaded from the internet to run PMDb on a desktop or laptop. Instructions on how to download VMware Player and launch PMDb are provided in Appendix D. Please note that the ISO image for Volume 1 must be burned onto a DVD disc to function properly. Volume 2: Sample Data is a CD that contains data collected from highway agencies to illustrate the use of PMDb. Instructions are provided in Appendix E.Help on Burning an .ISO CD-ROM (Warning: This is a large file and may take some time to download using a high-speed connection.)Software Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Transit Enterprise Architecture and Planning Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Transit Cooperative Research Program (TCRP) Report 84, e-Transit: Electronic Business Strategies for Public Transportation, Volume 9, Transit Enterprise Architecture and Planning Framework presents multi-faceted methods, tools, and examples within a framework to help transit agencies successfully implement technologies.The report describes the connections between a transit agency’s business and the technology, assists with building the business case for specific investments, highlights different financing options, provides guidance on an enterprise-wide approach to create more efficient and effective system deployments, and provides a method to show the benefits of a technology investment.The report provides a framework that incorporates five systems management disciplines: Enterprise Architecture Planning, Business Case Methodology, Systems Engineering, Financial Implementation Methods, and Post-Implementation Assessment.The declining costs of communications, data storage, and data retrieval are accelerating the opportunities spawned by the Internet and other information and communications technologies. Choosing and sequencing investments in technologies, processes, and people to reduce costs and increase productivity present challenges to the transit manager, who must weigh the costs, benefits, and risks of changing the ways services are delivered. To assist in meeting such challenges, the TCRP Report 84: e-Transit: Electronic Business Strategies for Public Transportation series documents principles, techniques, and strategies that are used in electronic business for public transportation.
Keywords: Transportation and Infrastructure

A Framework for Improving Travel Time Reliability - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-L17-RW-1: A Framework for Improving Travel Time Reliability describes the results of a project designed to identify and enhance the dissemination of transportation systems management and operations (TSM&O) information.A major component of Reliability Project L17 was development of a Knowledge Transfer System (KTS), a web-based tool designed to provide convenient one-stop access to the complete range of TSM&O information. The KTS tool is currently available.Reliability Project L17 also produced the following six items to fill in gaps in knowledge about transportation systems management and operations:Gap-Filling Project 1: CEO Briefing Book on Effective Operations Improvement StrategiesGap-Filling Project 2: Deployment Guidance for TSM&O StrategiesGap-Filling Project 3: Best Practices for TSM&O Program and Budget DevelopmentGap-Filling Project 4: A Guidebook for Standard Reporting and Evaluation Procedures for TSM&O StrategiesGap-Filling Project 5: Guidebook: Placing a Value on Time ReliabilityGap-Filling Project 6: Business Case Primer Communicating the Value of Transportation Systems Management and Operations
Keywords: Transportation and Infrastructure

Synthesis of Information Related to Transit Problems: 2012 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 104: Synthesis of Information Related to Transit Problems is a digest of the progress and status of TCRP Project J-7, “Synthesis of Information Related to Transit Problems,” for which the Transportation Research Board is the agency conducting the research.
Keywords: Transportation and Infrastructure